Complications of Arterio-Venous Fistula in Patients Undergoing Haemodialysis - Agrawaal, Krishna Kumar (Journal of Nepal Health Research Council, 2023)
Background: Vascular access is required for hemodialysis and arterio-venous fistula is the preferred access. Various guidelines have recommended monitoring and surveillance of arterio-venous fistula as the standard of care. This study looked into usefulness of clinical examination to detect complications of arterio-venous fistula. Methods: The study was conducted in the from February 2022 till September 2022 under Nephrology unit, Departement of Internal Medicine at Universal College of Medical Sciences. Ethical clearance was taken. Patients undergoing hemodialysis were enrolled in the study. After informed and written consent, clinical examination of arterio-venous fistula was done by look, listen and feel method. Data was collected as per the approved performa. Statistical analysis was done using Statistical Package for the Social Sciences software version 17. Results: Total enrolled study population was 73. Mean age of the study population was 47.45 years ± 14.60 years with a Male: Female ratio of 1.3:1. Complications were seen in a total of 33 patients with an overall rate of 45.2%. The mean duration of AVF creation was 32.68 ± 24.56 months. Most common complication of arterio-venous fistula was overall stenosis 18 (24.7%). Conclusions: There is a higher rate of complications of arterio-venous fistula. Monitoring and surveillance of arterio-venous fistula should be performed as a standard of care in every hemodialysis centre. Keywords: Arterio-venous fistula; complication; hemodialysis